Teacher's Perception of Learning Tools through Realistic Mathematics Education with Islamic Context on Social Arithmetic Materials - Cut Morina Zubainur; Mardhiati Mardhiati; Anwar Anwar (research, training and philanthropy institution Natural Aceh, 2022)
This study aims to determine the teacher's perception of learning tools through realistic mathematics education with an Islamic context on social arithmetic material. This research uses descriptive-analytical research with a qualitative approach. The research subjects were two mathematics teachers at MTsS Darul Hikmah in West Aceh, two mathematics teachers at MTsS Safinatun Naja in Nagan Raya, and three mathematics teachers at MAS Darul Hikmah in West Aceh. The data collection technique used an open questionnaire instrument. The data analysis technique uses the Miles and Huberman model which consists of data reduction, data presentation, and drawing conclusions. The results showed that seven teachers (100%) had never participated in using learning tools through realistic mathematics education with an Islamic context on social arithmetic material, five (71%) of the seven teachers were interested in using the learning tools, six (86%) of the seven teachers interested and agree with the learning tools in question, and seven teachers (100%) are willing and express their willingness to use the learning tools in question to students optimally. Based on the findings above, it can be concluded that the majority of teachers stated that the learning tools needed to be developed to support the vision and mission of the school. So, teachers and students need learning tools through realistic mathematics education with an Islamic context that lead students to understand social arithmetic based on the realities of everyday life that are integrated with Islamic values.